Majalah Suara Muhammadiyah sebagai Amal Usaha dalam Mendukung Dakwah Islam di Era Modern Satu Kajian Deskriptif - Arditya Prayogi; Irham Irham; Rizal Ilham Ramadhan; Syarifan Nurjan; Anip Dwi Saputro (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Muhammadiyah, as one of the largest Islamic organizations in Indonesia, has used various media to spread da'wah since its inception. Suara Muhammadiyah (SM) magazine, first published in 1915, has become an important instrument in supporting the organization's da'wah mission. This study aims to analyze the role of SM magazine as Muhammadiyah's charitable endeavor in the field of da'wah and its relevance in the development of the era. The study uses a literature review approach and qualitative descriptive methods by analyzing various primary and secondary sources related to SM and the context of Muhammadiyah's da'wah. The results of the study show that SM has played a role as a medium to purify Islamic teachings, promote educational modernization, and build national awareness since the pre-independence era to the digital era. This magazine not only conveys religious messages, but also encourages readers to think critically, understand global issues, and adapt to technological advances. In facing the challenges of the digital era, SM has succeeded in maintaining its existence through innovation, such as the use of digital platforms and social media, which allow the dissemination of da'wah messages to a wider audience, including the younger generation. The implications of this study indicate that Muhammadiyah's success in utilizing media as a means of da'wah can be a model for other organizations. SM's consistency in conveying moderate and progressive Islamic messages illustrates how traditional print media can adapt and remain relevant amidst technological developments. This study also emphasizes the importance of synergy between Islamic values, media innovation, and the needs of modern society in supporting inclusive and wide-reaching da'wah.